2004
DOI: 10.1111/j.1553-2712.2004.tb02204.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Phenytoin-loading Techniques in the Emergency Department

Abstract: Objectives: To compare the effectivenesses of three phenytoin-loading techniques. Methods: Patients with subtherapeutic phenytoin concentrations who presented within 48 hours of a seizure were randomized to receive either 20 mg/ kg of oral phenytoin (PO), divided in maximum doses of 400 mg every two hours, 18 mg/kg of intravenous phenytoin (IVP) at an initial infusion rate of 50 mg/min, or 18 mg/kg (phenytoin equivalents) of intravenous fosphenytoin (IVF) at an initial infusion rate of 150 mg/min. Results: A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Data comparing intravenous phenytoin and fosphenytoin have shown that the latter also causes cardiotoxicity, suggesting that the solvent is not the culprit. [2223] A consensus guideline recommended that intravenous phenytoin should be avoided in patients with cardiovascular disease or when symptoms of debilitating illness, emaciation, hyponatremia, peripheral vascular disease, hemodynamic instability, or sepsis coexist. [24] The increased mortality due to prehospital phenytoin might have resulted from failure to recognize these complications in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Data comparing intravenous phenytoin and fosphenytoin have shown that the latter also causes cardiotoxicity, suggesting that the solvent is not the culprit. [2223] A consensus guideline recommended that intravenous phenytoin should be avoided in patients with cardiovascular disease or when symptoms of debilitating illness, emaciation, hyponatremia, peripheral vascular disease, hemodynamic instability, or sepsis coexist. [24] The increased mortality due to prehospital phenytoin might have resulted from failure to recognize these complications in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Although FPHT exhibits a lower incidence of adverse reactions, it can still cause blood pressure reduction and arrhythmia, which is an issue. [5,6] …”
Section: Introductionmentioning
confidence: 99%
“…Patients with contraindications may be at risk for phenytoin toxicity after administration. This is compounded by the fact that adverse drug effects can be influenced by route of administration (13). Additionally, patients not currently taking any seizure medication may be prescribed phenytoin by an emergency physician for long-term seizure management.…”
Section: Discussionmentioning
confidence: 98%